Visualizing Personal Branding: A Multimodal Analysis of 'Flexing' in Instagram - Brahmana, Christanta Rejuna Phanes S; Ningrum, Dwi Kurnia Surya; Perangin-angin, Alemina Br. (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study delves into the dynamic phenomenon of "flexing" in personal branding, focusing on online store owners and their strategic utilization of this behaviour on Instagram. This study employs qualitative research methods to analyze the multimodal elements that constitute "flexing" and its implications within online store owners. Findings reveal that "flexing" is not merely an exhibition of wealth but a powerful tool wielded by online store owners to strengthen their personal branding efforts. This strategic use of "flexing" has the potential to increase brand recognition, customer engagement, and sales. The study not only contributes to the understanding of this aspect of online entrepreneurship but also underscores the importance of multimodal analysis in deciphering the complexities of digital personal branding. These findings will inspire further exploration in this field and encourage online entrepreneurs to harness "flexing" for enhancing their online presence and businessÂ prosperity.